GHG emission reduction measures and alternative fuels in different shipping segments and time horizons – A Delphi study - Hellström, Magnus; Rabetino, Rodrigo; Schwartz, Henry; Tsvetkova, Anastasia; Syed, Hammad Ul Haq (Elsevier, 2024)
The bodies governing the global maritime industry have set short- and long-term targets for reducing GHG emissions from shipping. Various emission abatement measures exist, but their applicability in different contexts widely varies. The situation is unclear, especially for the so-called alternative fuels. These fuels hold the biggest emission reduction potential. Conversely, they are expensive, and the feasibility of investments in those technologies has high uncertainty. Despite a growing body of knowledge on the characteristics and potential of alternative fuels, no consensus exists as to which fuels would be best for each segment of the maritime industry – in the near future and the long run. We contribute with a Delphi study to fill this gap. Our results pinpoint the differences between the shipping segments and the short- and long-term choices for alternative fuels.
Keywords: Alternative fuels; Decarbonisation; Delphi study; Emission reduction; Maritime industry; shipping; fi=Strateginen johtaminen|en=Strategic Management|